Languishing and flourishing experiences in schizophrenic patients during hospitalization - Fathinah, Amirah; Istiningtyas, Listya; Situmorang, Dominikus David Biondi (Psikohumaniora: Jurnal Penelitian Psikologi, 2023)
Hospitalization affects the emotional, psychological, and social well-being of schizophrenic patients. The process can produce experiences of both flourishing and languishing. This study aims to identify and describe such experiences of schizophrenic patients during hospitalization. A phenomenological qualitative method was employed with six schizophrenic patients hospitalized at Ernaldi Bahar Hospital in Palembang, Indonesia. Research data were collected using semi-structured interviews and documentation methods. These were analyzed using thematic analysis. The findings demonstrate the developing experiences of schizophrenic patients during hospitalization; there are three themes: 1) experiencing increased contact with and awareness of reality, 2) finding meaning and purpose in life, and 3) finding positive relationships among patients. Languishing experiences were also classified into three themes: 1) feeling bored and confined, 2) experiencing unpleasant events on arrival, and 3) experiencing social isolation. In particular, clinical struggle, functional recovery, and cultural struggle are predictors of the flourishing and languishing experiences of hospitalized schizophrenic patients. The findings contribute to developing the concept of languishing and flourishing among such patients through evidence-based empirical data regarding the efforts to foster and maintain their subjective well-being during hospitalization.